Alliance Entrepreneurship and Entrepreneurial Orientation: The Mediating Effect of Knowledge Transfer - Rezazadeh, Arash; Mahjoub, Mahsa (Gadjah Mada International Journal of Business, 2016)
Today’s rapidly changing business environment has impelled companies to cooperate with their competitors in order to gain more competitive advantages through a win-win situation. Thereby, building alliances is one of the cooperative strategies that have been adopted by many enterprises, consequently attracting great attention from scholars. However, the literature about alliances seems to lack studies in the domain of entrepreneurship. Accordingly, this paper aims to extend entrepreneurship into the field of alliances by highlighting two phenomenal concepts: alliance entrepreneurship, and entrepreneurial orientation. Hence, the relationship between these two constructs, together with the mediating role of knowledge transfer between alliance partners, is investigated. Employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique we analyze a set of data from the automotive industry and its sub-sectors. The results confirm the significant positive effect of alliance entrepreneurship on partners’ entrepreneurial orientation, as well as the mediating effect of knowledge transfer.